Influence Tax Knowledge, Taxpayer Awareness, Quality Services and Sanctions Taxation to Taxpayer Compliance - Hanifah, Faridatul; Eka Febriani, Defha; Prastiya, Rista; Umi Latifatul Asnab, Fajar; Lazuardi Firdaus, Ahmad; Amrulloh, Amri (Inovasi Analisis Data, 2024)
This research aims to determine the influence of tax knowledge, taxpayer awareness, service quality and tax sanctions on individual taxpayer compliance. This research was conducted at Madiun State Polytechnic. This type of research is quantitative research. This research uses the Slovin formula to determine the sample size of 85 individual taxpayers at the Madiun State Polytechnic, using a purposive sampling method. The analysis technique used is multiple linear regression. The research results show that tax knowledge and service quality have a positive effect on taxpayer compliance because the higher the level of knowledge and quality of tax services, the easier it is for taxpayers to understand tax regulations and fulfill their tax obligations. Taxpayer awareness does not affect taxpayer compliance because the increase in incidents that frequently occur, especially in the taxation sector, means that taxpayers do not want the taxes they pay to be misused by the tax authorities themselves, so that taxpayer compliance does not increase. Tax sanctions have no effect on mandatory tax compliance because there is still a lack of public awareness of the importance of taxes for smooth development which affects individual taxpayer compliance does not increase.